2006
DOI: 10.1152/jn.01261.2005
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Resolution for Feature Binding Is Impaired in Peripheral and Amblyopic Vision

Abstract: Neri, Peter and Dennis M. Levi. Spatial resolution for feature binding is impaired in peripheral and amblyopic vision. J Neurophysiol 96: 142-153, 2006. First published January 18, 2006 doi:10.1152/jn.01261.2005. We measured spatial resolution for discriminating targets that differed from nearby distractors in either color or orientation or their conjunction. In the fovea of normal human observers, whenever both attributes are big enough to be individually visible, their conjunction is also visible. In the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 68 publications
(76 reference statements)
3
34
0
Order By: Relevance
“…In other words, the deleterious effects of crowding on position encoding can be accounted for by simple recourse to the inherent positional uncertainty in the peripheral visual field (18)(19)(20). This aspect of our model is similar to a recent model of feature binding (37), where the high positional noise in the periphery causes target features to be erroneously associated with adjacent elements within coarse feature maps. Additionally, because there are also intrinsic levels of uncertainty in other domains affected by crowding (3-6), such as orientation (38) and direction (39), our model raises the intriguing possibility that crowding could involve the averaging of features across all affected modalities, as opposed to the addition of noise suggested by the historic focus on error rates in crowding tasks.…”
Section: Discussionsupporting
confidence: 58%
“…In other words, the deleterious effects of crowding on position encoding can be accounted for by simple recourse to the inherent positional uncertainty in the peripheral visual field (18)(19)(20). This aspect of our model is similar to a recent model of feature binding (37), where the high positional noise in the periphery causes target features to be erroneously associated with adjacent elements within coarse feature maps. Additionally, because there are also intrinsic levels of uncertainty in other domains affected by crowding (3-6), such as orientation (38) and direction (39), our model raises the intriguing possibility that crowding could involve the averaging of features across all affected modalities, as opposed to the addition of noise suggested by the historic focus on error rates in crowding tasks.…”
Section: Discussionsupporting
confidence: 58%
“…Our quantitative results illustrate an important aspect of the anomalous contextual interactions underlying crowding that has not been fully explored empirically: diminished binding of target features 35 due to proximal weakening of connectivity combined with inappropriate and spurious binding of distracter features due to distal strengthening of connectivity in the lateral interaction zone. This dual nature of the binding deficiency explains our previous finding with classification images that crowding reduces the use of valid features while at the same increasing the number of invalid features used by the visual system 5 .…”
Section: Discussionmentioning
confidence: 83%
“…Allocating spatial attention has been hypothesized as a possible function of the pulvinar (Bender and Youakim 2001; Petersen, et al 1987), and with the spatial resolution reported here of 0.05E or better (where E is the eccentricity from fixation), highly precise spatial attention could be supported by the right hemisphere pulvinar. Neri and Levi (2006) report the resolution of feature binding at about 0.11E for a dense stimulus array and about 0.06E for a sparse array, so the precision of spatial coding in the pulvinar is also fine enough to account for these data. If the pulvinar is involved in feature binding, the coarser resolution for feature binding could be due to downstream noise, or to wiring scatter as proposed by Neri & Levi (2006).…”
Section: Discussionmentioning
confidence: 93%
“…Neri and Levi (2006) report the resolution of feature binding at about 0.11E for a dense stimulus array and about 0.06E for a sparse array, so the precision of spatial coding in the pulvinar is also fine enough to account for these data. If the pulvinar is involved in feature binding, the coarser resolution for feature binding could be due to downstream noise, or to wiring scatter as proposed by Neri & Levi (2006). The lateralization that we report is consistent with several previous findings, including the implication of the pulvinar in spatial neglect (Karnath, et al 2002) and the prospect that spatial attention is dominated by the right hemisphere (Mapstone, et al 2003; Mesulam 1999).…”
Section: Discussionmentioning
confidence: 93%